Conductive hydrogel for promoting bone growth as well as preparation method and application thereof
By using methacrylic anhydride gelatin copper nanoparticle conductive hydrogel as bone tissue engineering scaffold material, the problem of insufficient biocompatibility and mechanical properties of existing bone defect repair materials is solved, and significant bone regeneration efficiency and biocompatibility are achieved.
Patent Information
- Application Number
- CN202411857449.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
Existing bone defect repair materials have problems with insufficient biocompatibility and mechanical properties, which are difficult to effectively promote bone regeneration.
Methacrylic anhydride gelatin copper nanoparticle conductive hydrogel is used as a scaffold material for bone tissue engineering, and prepared by photocrosslinking technology. Combining the conductive properties of copper nanoparticles and the biocompatibility of methacrylic anhydride gelatin, a hydrogel with good pore structure, mechanical properties and conductive properties is formed.
This material can significantly promote the proliferation and differentiation of bone cells, improve bone regeneration efficiency, have good biocompatibility and low cytotoxicity, and is suitable for bone defect repair.
Smart Images

Figure CN119680007A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical technology, and in particular to a conductive hydrogel for promoting bone growth, and a preparation method and application thereof. Background Art
[0002] Clinically, large-scale maxillofacial bone defects caused by trauma, tumors, inflammation, etc. will seriously affect the patient's quality of life from both physiological and psychological aspects, which is a very difficult problem. For bone defects, how to regenerate bone needs to be solved urgently. Bone substitute materials have been developed to promote the repair of bone defects and have great clinical potential, but there are still certain problems. Therefore, finding a new type of bone defect repair material that is biocompatible and degradable has become an urgent clinical need. Electroactive hydrogels have shown great potential in the application of clinical bone defects. Electroactive hydrogels are a type of intelligent material with electrical stimulation response characteristics. It can simulate the force-electric properties of bones, thereby generating corresponding electrical signals or deformations when stimulated by an electric field. This material combines the biocompatibility and injectability of hydrogels with the responsiveness of electroactive substances, providing a new idea for bone defect repair.
[0003] Electroactive hydrogels can simulate the mechanical-electrical environment of bones, promote the proliferation and differentiation of bone cells through electrical stimulation, and thus accelerate the repair of bone defects. Studies have shown that hydrogels with piezoelectric properties can generate electrical signals when subjected to external forces. These signals can stimulate the activity of bone cells and promote the formation of new bones.
[0004] The injectability of electroactive hydrogels allows them to be easily filled into bone defects to form a repair material that is tightly integrated with the surrounding bone tissue. In addition, by adjusting the degradation rate and mechanical properties of the hydrogel, it can be matched with the bone regeneration rate, further improving the repair efficiency.
[0005] Compared with traditional bone transplantation methods, electroactive hydrogels have lower immunogenicity and better biocompatibility, and can reduce the occurrence of complications such as postoperative infection and rejection.
[0006] Conductive hydrogels improve their electrical conductivity by introducing conductive substances (such as metal nanoparticles, carbon nanotubes, etc.). This hydrogel can be used as an electrode material in electrical stimulation therapy to promote bone regeneration by applying electrical stimulation to the bone defect site. Although electroactive hydrogels have shown great potential in bone defect repair, their clinical application still faces some challenges. For example, how to further improve the mechanical properties and stability of hydrogels, and how to accurately control the conditions and parameters of electrical stimulation. In the future, with the continuous development of materials science and biomedical technology, electroactive hydrogels are expected to play a greater role in the field of bone defect repair. Summary of the invention
[0007] In order to solve the above technical problems, the first purpose of the present invention is to provide a method for preparing a conductive hydrogel that promotes bone growth, the second purpose is to provide a conductive hydrogel that promotes bone growth, and the third purpose is to provide its application. The hydrogel has good electrical conductivity, pore structure, biocompatibility, and mechanical properties, and has a good osteogenesis-promoting effect. Its preparation process is simple and highly repeatable.
[0008] To achieve the above first objective, the present invention is implemented by the following technical scheme: A method for preparing a conductive hydrogel that promotes bone growth, characterized in that it is prepared according to the following steps:
[0009] (1) Preparing a methacrylic anhydride gelatin hydrogel prepolymer solution, dissolving a photoinitiator in deionized water to prepare a solution with a mass volume concentration of 0.003 to 0.005 g / mL; dissolving methacrylic anhydride gelatin Gelma in the solution to prepare a methacrylic anhydride gelatin hydrogel prepolymer solution; and improving its dispersibility and stability through the dispersion technology.
[0010] (2) preparing a CuNPs dispersion, adding copper nanoparticles into deionized water, and stirring the mixture to obtain a copper nanoparticle dispersion;
[0011] (3) Preparation of photo-cross-linked hydrogel: Mix methacrylated gelatin prepolymer solution and CuNPs dispersion solution to prepare methacrylated gelatin copper nanoparticle conductive hydrogel mixture; in the mixture, the mass volume concentration of methacrylated gelatin is kept constant at 0.05 g / mL, and the concentration of copper nanoparticles is 10 mmol / L-40 mmol / L. After removing bubbles, the mixed solution is added into a mold and irradiated with ultraviolet light to prepare photo-cross-linked hydrogel.
[0012] The particle size of the copper nanoparticles is 10-30 nm.
[0013] In the above scheme, the substitution degree of the methacrylic anhydride gelatin is 55-65%, thereby ensuring its biocompatibility and forming performance.
[0014] In the above scheme: the concentration of the methacrylic anhydride gelatin hydrogel prepolymer solution is 0.1 g / mL.
[0015] In the above scheme: the concentration of the CuNPs dispersion is 20mmol / L-80mmol / L, and the methacrylic anhydride gelatin prepolymer solution and the CuNPs dispersion are mixed in a volume ratio of 1:1.
[0016] In the above scheme, the ultraviolet irradiation time is 45-60s, and the wavelength is 405nm. The hydrogel material with ideal mechanical properties and conductive properties can be obtained by adjusting the wavelength and irradiation time.
[0017] In the above scheme: the photoinitiator is LAP.
[0018] A conductive hydrogel for promoting bone growth is prepared by the method for preparing the conductive hydrogel for promoting bone growth.
[0019] A use of the conductive hydrogel that promotes bone growth as a bone filling material for the treatment of bone defect repair.
[0020] The present invention uses methacrylic anhydride gelatin copper nanoparticle conductive hydrogel as a bone tissue engineering scaffold material, and ensures that the hydrogel scaffold material has good pore structure, biocompatibility, conductive properties, mechanical properties and biological activity through the composition and proportion of the methacrylic anhydride gelatin copper nanoparticle conductive hydrogel, and can support cell growth and osteogenic differentiation in the hydrogel scaffold material.
[0021] GelMA is mixed with CuNPs dispersion, and under the action of photoinitiator LAP, the components are uniformly compounded through physical and chemical methods, and the hydrogel is given conductive properties; cross-linking and curing. GelMA is cross-linked and cured under ultraviolet light to form a GelMA-CuNPs conductive hydrogel with a three-dimensional network structure and conductive properties.
[0022] The hydrogel has excellent biocompatibility, antibacterial properties and electrical conductivity, and is suitable for use in tissue engineering, cell culture, bioengineering and other fields.
[0023] This hydrogel can be used as a cell scaffold material to promote cell growth and differentiation; at the same time, its conductive properties can be used to monitor cell activity and physiological state, providing a new means for biomedical research.
[0024] The hydrogel can load cells for cell culture and can also load growth factors to promote osteogenic differentiation of cells, and can be used as a bone filling material for the treatment and research of bone defect repair.
[0025] The photo-crosslinked hydrogel prepared by the present invention has the following better effects in addition to the morphology, water absorption performance and plasticity of traditional hydrogels:
[0026] 1. The present invention processes and modifies methacrylic anhydride gelatin and introduces copper nanoparticles to prepare a stable photo-crosslinked hydrogel with good mechanical strength and biological properties.
[0027] 2. The photo-crosslinked hydrogel of the present invention has certain antibacterial and conductive properties by adding appropriate CuNPs.
[0028] 3. The product of the present invention selects appropriate illumination time and wavelength to obtain a hydrogel material with ideal mechanical properties and conductive properties. By using different molds, rapid preparation of photo-crosslinked hydrogels of different shapes and thicknesses can be achieved.
[0029] 4. The photocross-linked hydrogel prepared by the present invention has a three-dimensional porous structure, which is suitable for cell adhesion and growth; it has good biocompatibility, degradation performance and low cytotoxicity, and is suitable for cell growth and proliferation; it has good mechanical properties, can withstand the pressure generated in physiological activities, and can promote cell osteogenic differentiation. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Photocuring cross-linking process of methacrylic anhydride-treated gelatin copper nanoparticle conductive hydrogel.
[0031] Figure 2 This is a scanning electron micrograph of methacrylic anhydride-treated gelatin copper nanoparticle conductive hydrogel (from left to right: Gelma, Gelma-CuNPS hydrogel), proving that after the addition of copper nanoparticles, the hydrogel has a loose and porous structure.
[0032] Figure 3 Results of the conductivity experiment on methacrylic anhydride-treated gelatin copper nanoparticle conductive hydrogel.
[0033] Figure 4 This is a diagram of the live and dead cell staining and CCK8 experimental results of methacrylic anhydride gelatin copper nanoparticle conductive hydrogel.
[0034] Figure 5 This is the antibacterial experimental results of methacrylic anhydride gelatin copper nanoparticle conductive hydrogel.
[0035] Figure 6 Micro-CT of methacrylated gelatin copper nanoparticle conductive hydrogel implanted in a mouse calvarial infected bone defect model after 4 weeks of implantation.
[0036] Figure 7 H&E staining and Masson staining of methacrylated gelatin copper nanoparticle conductive hydrogel implanted in the mouse skull infected bone defect model for 4 weeks DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0038] Example 1: Preparation of Methacrylic Anhydride-Conductive Copper Gelatin Hydrogel
[0039] 1. Preparation of methacrylic anhydride gelatin hydrogel prepolymer solution: Dissolve the photoinitiator LAP in deionized water at 50°C to prepare a solution with a mass volume concentration of 0.005 g / mL. Dissolve methacrylic anhydride gelatin Gelma with a substitution degree of 55-65% in the solution to prepare a methacrylic anhydride gelatin hydrogel prepolymer solution with a mass volume concentration of 0.1 g / mL.
[0040] 2. Preparation of CuNPs dispersion: Copper nanoparticles (particle size, 10-30 nm) were prepared into deionized water (DI) solutions with concentrations of 20 mmol / L, 40 mmol / L, and 80 mmol / L, respectively, and the mixtures were stirred to obtain copper nanoparticle dispersions.
[0041] 3. Preparation of photo-crosslinked hydrogel: Mix methacrylic anhydride gelatin prepolymer and CuNPs dispersion in a ratio of 1:1 to prepare a methacrylic anhydride gelatin copper nanoparticle conductive hydrogel mixture. In each group of conductive hydrogel mixtures, the mass volume concentration of methacrylic anhydride gelatin remains unchanged at 0.05g / mL. The concentrations of copper nanoparticles are 10mmol / L, 20mmol / L, and 40mmol / L, respectively. Remove bubbles and add the mixed solution into the mold. Irradiate with ultraviolet light for 45s at a wavelength of 405nm to prepare a photo-crosslinked hydrogel.
[0042] Performance testing of methacrylic anhydride-containing gelatin copper nanoparticle conductive hydrogel
[0043] like Figure 2 As shown in the SEM image, after adding copper nanoparticles, the hydrogel has a loose and porous structure, which can provide suitable growth space for bone cells, and bone cells can adhere and grow well, which is convenient for cell growth and reproduction. And with the addition of copper nanoparticles, the pore size of the hydrogel gradually decreases, the pore uniformity gradually increases, and the stability of the material continues to improve.
[0044] like Figure 3 As shown in the figure, the electrical performance test proves that with the increase of copper nanoparticle content, the conductivity of the photo-crosslinked hydrogel increases to a certain extent. The addition of 10mmol / L copper nanoparticles can increase the conductivity of the hydrogel by two times. After adding copper nanoparticles, the conductivity of the hydrogel has been improved to a certain extent.
[0045] Example 2: Application of methacrylic anhydride gelatin copper nanoparticle conductive hydrogel
[0046] 1. Cell culture with methacrylic anhydride gelatin copper nanoparticles: The three synthesized hydrogels (the concentrations of copper nanoparticles were 10mmol / L, 20mmol / L, and 40mmol / L, respectively) were placed in cell well plates, and macrophages raw264.7 were digested from the culture dish and added to the cell well plates containing the hydrogels. DMEM basic culture medium containing 10% fetal bovine serum and 1% double antibody was added, and the cells were grown, proliferated, and differentiated therein.
[0047] like Figure 4 As shown in the figure, after cell culture on methacrylic anhydride gelatin copper nanoparticle hydrogel, live cell staining and CCK experiments were performed. The results of laser confocal microscopy showed that when 10mmol / L copper nanoparticles were added to the hydrogel, the cell morphology was close to that of cells growing in normal tissues. The prepared hydrogel had good biocompatibility and low cytotoxicity, and was suitable for cell adhesion and growth. When the concentration of copper nanoparticles exceeded 10mmol / L and reached 20mmol / L and 40mmol / L, it had certain cytotoxicity.
[0048] Methacrylic anhydride gelatin copper nanoparticle conductive hydrogel antibacterial experiment: The synthesized hydrogel (final copper nanoparticle content of 10mmol / L) was placed in a cell well plate, and 1×10 7 / mL of S. aureus and E. coli bacterial suspension was inoculated into the well plate and cultured on agar medium. After 2-4 hours, a certain amount of the sample to be tested in the well plate was taken, diluted to the same multiple, plated, and photographed. A certain amount of the sample to be tested in the well plate was taken, the picture was stained for bacterial live and dead, and observed with a confocal microscope. Figure 5 As shown, the conductive hydrogel with added copper nanoparticles has certain antibacterial properties.
[0049] In order to verify the biological effect of methacrylic anhydride gelatin copper nanoparticle conductive hydrogel, a 2.5 mm diameter drill was used to create a defect on the right parietal bone of mice. Then, 100 μL of a suspension containing 1×10^8 CFU / mL Staphylococcus aureus was filled in the defect area, and different hydrogel materials were implanted. The mice were randomly divided into a blank group, S. aureus (Staphylococcus aureus), S. aureus + CuNPS-GelMA, and S. aureus + CuNPS-GelMA (copper nanoparticle content of 10 mmol / L) + ES (ES represents external electrical stimulation, using a DS1102Z-E oscilloscope (Puyuan Precision Electronics Co., Ltd.) with two needle-shaped metal electrodes connected by wires to provide external electric field stimulation (pulse electrical signal, 20 Hz, 100 mV mm -1), electrical stimulation was applied for 1 hour every other day). The mice were killed after 4 weeks, and skull samples were taken for Micro-CT scanning, HE staining, Masson staining and other tests to evaluate bone regeneration efficiency. Figure 6 and 7 As shown: The results showed that compared with the blank group and S. aureus, the bone repair in the defect area of the S. aureus + CuNPS-GelMA and S. aureus + CuNPS-GelMA + ES groups was significantly accelerated, proving that methacrylated gelatin copper nanoparticle conductive hydrogel has a certain osteogenic effect.
[0050] Example 3: Preparation of Methacrylic Anhydride-Conductive Hydrogel of Copper Nanoparticles of Gelatin
[0051] 1. Preparation of methacrylic anhydride gelatin hydrogel prepolymer solution: Dissolve the photoinitiator LAP in deionized water at 50°C to prepare a solution with a mass volume concentration of 0.005 g / mL. Dissolve methacrylic anhydride gelatin Gelma with a substitution degree of 55-65% in the solution to prepare a methacrylic anhydride gelatin hydrogel prepolymer solution with a mass volume concentration of 0.1 g / mL.
[0052] 2. Preparation of CuNPs dispersion: Copper nanoparticles (particle size, 10-30 nm) were separately prepared into a deionized water (DI) solution with a concentration of 20 mmol / L, and the mixture was stirred to obtain a copper nanoparticle dispersion.
[0053] 3. Preparation of photo-crosslinked hydrogel: Mix methacrylic anhydride gelatin prepolymer and CuNPs dispersion in a ratio of 1:1 to prepare a methacrylic anhydride gelatin copper nanoparticle conductive hydrogel mixture. In each group of conductive hydrogel mixtures, the mass volume concentration of methacrylic anhydride gelatin remains unchanged at 0.05g / mL. The concentration of copper nanoparticles is 10mmol / L. Remove bubbles and add the mixed solution into the mold. Irradiate with ultraviolet light for 60s to prepare a photo-crosslinked hydrogel.
[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a conductive hydrogel for promoting bone growth, characterized in that: Prepare according to the following steps: (1) preparing a methacrylic anhydride gelatin hydrogel prepolymer solution, dissolving a photoinitiator in deionized water to prepare a solution with a mass volume concentration of 0.003 to 0.005 g / mL; dissolving methacrylic anhydride gelatin Gelma in the solution to prepare a methacrylic anhydride gelatin hydrogel prepolymer solution; (2) preparing a CuNPs dispersion, adding copper nanoparticles into deionized water, and stirring the mixture to obtain a copper nanoparticle dispersion; (3) Preparation of photo-cross-linked hydrogel: Mix methacrylated gelatin prepolymer solution and CuNPs dispersion solution to prepare methacrylated gelatin copper nanoparticle conductive hydrogel mixture; in the mixture, the mass volume concentration of methacrylated gelatin is kept constant at 0.05 g / mL, and the concentration of copper nanoparticles is 10 mmol / L-40 mmol / L. After removing bubbles, the mixed solution is added into a mold and irradiated with ultraviolet light to prepare photo-cross-linked hydrogel.
2. The method for preparing the conductive hydrogel for promoting bone growth according to claim 1, characterized in that: The degree of substitution of the methacrylic anhydride gelatin is 55-65%.
3. The method for preparing the conductive hydrogel for promoting bone growth according to claim 1 or 2, characterized in that: The concentration of the methacrylic anhydride gelatin hydrogel prepolymer solution is 0.1 g / mL.
4. The method for preparing the conductive hydrogel for promoting bone growth according to claim 3, characterized in that: The concentration of the CuNPs dispersion is 20 mmol / L-80 mmol / L, and the methacrylic anhydride gelatin prepolymer solution and the CuNPs dispersion are mixed in a volume ratio of 1:
1.
5. The method for preparing the conductive hydrogel for promoting bone growth according to claim 4, characterized in that: The UV irradiation time is 45-60s, and the UV wavelength is 405nm.
6. The method for preparing the conductive hydrogel for promoting bone growth according to claim 1, characterized in that: The photoinitiator is LAP.
7. A conductive hydrogel for promoting bone growth prepared by the method for preparing a conductive hydrogel for promoting bone growth according to any one of claims 1 to 6.
8. Use of the conductive hydrogel for promoting bone growth according to claim 7 as a bone filling material for the treatment of bone defect repair.
Citation Information
Cited By
Injectable piezoelectric ion hydrogel precursor solution, injectable piezoelectric ion hydrogel and application
CN121490136A
Injectable piezoelectric ionic hydrogel precursor solution and injectable piezoelectric ionic hydrogel and applications
CN121490136B